Preparation method and application of nitrogen-doped closed-pore structure petroleum coke carbon negative electrode material
By alkali activation and nitrogen doping coating treatment on petroleum coke, nitrogen-doped closed-porous structure petroleum coke carbon material was prepared, which solved the problem of poor sodium storage performance of traditional graphite anode materials in sodium ion batteries, and achieved efficient Sodium ion insertion and detachment and good cycling stability.
Patent Information
- Application Number
- CN202411183358.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional graphite negative electrode materials are not conducive to the embedding and removal of sodium ions in sodium ion batteries, resulting in poor sodium storage performance, limiting the application of petroleum coke-based carbon materials in sodium ion batteries.
Active porous carbon is prepared by alkali activation of petroleum coke, and nitrogen-containing coating agent is added to the active porous carbon for nitrogen doping and coating, and then nitrogen-doped closed-porous structure petroleum coke carbon material is prepared by high temperature carbonization.
The reversible specific capacity and Coulomb efficiency of petroleum coke materials have been improved, good sodium storage performance and cycle stability have been achieved, and good development prospects have been achieved.
Smart Images

Figure CN119480945A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery electrode materials, and in particular to a preparation method and application of a nitrogen-doped closed-pore petroleum coke negative electrode material. Background Art
[0002] Sodium-ion batteries (SIBs) are considered to be the next generation of energy storage technology with broad application prospects due to their abundant resources, low cost and environmental friendliness. Among the negative electrode materials of sodium-ion batteries, carbon-based materials have become a hot topic of research due to their stable electrochemical properties, high theoretical specific capacity and low cost. However, due to thermodynamic and kinetic limitations, traditional graphite negative electrodes are not conducive to the insertion and extraction of sodium ions, and have poor sodium storage performance. Therefore, finding low-cost carbon negative electrode materials with suitable sodium storage structures has become the key to the large-scale application of sodium-ion batteries.
[0003] As a byproduct of the petroleum industry, petroleum coke has the characteristics of high carbon content, wide sources and low cost, and is an ideal precursor for preparing carbon negative electrode materials for sodium ion batteries. However, due to the regular microstructure and few sodium storage active sites of petroleum coke-based carbon materials, when used as negative electrodes for sodium ion batteries, there are challenges such as low sodium storage capacity, low coulombic efficiency and unstable structure, which seriously limits the application of petroleum coke-based carbon materials in sodium ion batteries.
[0004] Recently, researchers have found that the petroleum coke-based carbon materials obtained by doping petroleum coke with elements such as N / S / P have abundant active sites and exhibit good sodium storage performance. For example, in the patent "High-sulfur petroleum coke-derived porous carbon, its preparation method, electrode material and sodium ion battery" (application number CN202211314167.6), petroleum coke is acidified and then directly calcined at high temperature to obtain N / S-doped porous carbon negative electrode materials, which significantly improves the sodium storage performance of petroleum coke-based carbon materials. However, the reversible specific capacity of porous carbon obtained by simple N / S doping is only 250mAh g -1 . In addition, introducing too many surface defects through doping usually leads to a low first efficiency of carbon negative electrode materials. For example, in the patent "A low-temperature petroleum coke negative electrode material with a nitrogen-containing polymer pyrolysis carbon coated on the surface and its preparation method" (application number CN201710076274), a carbon material obtained by low-temperature pyrolysis of a nitrogen-containing polymer coated on the surface of petroleum coke achieves a good lithium storage capacity in a lithium-ion battery, but its highest first efficiency is only 64.2%. In order to solve the above problems, this patent first obtains active porous carbon by alkali activation of petroleum coke, and then adds a nitrogen-containing coating agent to simultaneously dope and coat the active porous carbon with nitrogen, and then obtains a nitrogen-doped closed-cell petroleum coke carbon material through high-temperature carbonization, so that its reversible specific capacity can reach up to 352.8mAh g -1At the same time, the first coulombic efficiency is maintained at 81.3%, and it has good cycle stability, which effectively improves the electrochemical properties of petroleum coke carbon materials, realizes high added value utilization of petroleum coke, and has good development prospects. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a nitrogen-doped closed-pore petroleum coke negative electrode material and its application, wherein the method realizes the preparation of low-value petroleum coke into a negative electrode material with excellent sodium storage performance and stable structure.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a nitrogen-doped closed-pore petroleum coke negative electrode material and its application, comprising the following steps:
[0008] Activation step: grind and mix the petroleum coke and the alkali activator and place them under inert atmosphere for high temperature activation pretreatment. The product after high temperature treatment is pickled with hydrochloric acid to obtain a carbon material with a developed open pore structure.
[0009] Doping and coating step: Add the prepared carbon material with developed open-pore structure and coating agent dopamine hydrochloride into an alkaline buffer solution, mix and stir at room temperature for reaction, and wash until the pH is neutral after the reaction is completed. Carbonize the above-mentioned coated product at high temperature under inert conditions to obtain a nitrogen-doped closed-pore structure carbon material.
[0010] The petroleum coke is spherical calcined coke, and any one of high-sulfur coke, medium-sulfur coke and low-sulfur coke can be selected.
[0011] The activator can be sodium hydroxide or potassium hydroxide, and the mass ratio of petroleum coke to the alkali activating agent is 1:0.5-1:4;
[0012] Preferably, the mass ratio of the petroleum coke to the activation reagent is 1:1-1:3;
[0013] The temperature of the high temperature activation pretreatment is 400-900°C and the time is 1-3h;
[0014] Preferably, the high-temperature activation pretreatment is carried out in an inert atmosphere, and the gas of the inert atmosphere is nitrogen, helium or argon;
[0015] Preferably, the heating rate to the high temperature activation temperature is 2-10°C / min.
[0016] The doping coating reagent is dopamine hydrochloride;
[0017] The mass ratio of the activated product to the coating reagent is 1:1-1:6;
[0018] The activated product and the coating reagent are mixed and stirred in an alkaline buffer solution at room temperature for 10-40 hours at a stirring speed of 200-800 r / min.
[0019] The alkaline solution is Tris-HCl buffer.
[0020] The carbonization temperature of the coated product is 800-1600° C., preferably 1200-1400° C., and the insulation time is 1-3 hours.
[0021] Preferably, the heating rate to the high temperature carbonization treatment temperature is 2-10°C / min.
[0022] Preferably, the atmosphere of the high-temperature carbonization treatment is an inert atmosphere.
[0023] The gas of the inert atmosphere is nitrogen, helium or argon.
[0024] The present invention provides a nitrogen-doped closed-pore petroleum coke carbon material prepared by the method described in the above technical solution, and the pore volume is 0.01-0.03cm 3 g -1 , with a specific surface area of 1-25m 2 g -1 The (002) crystal plane interlayer spacing of the nitrogen-doped closed-cell petroleum coke carbon material is 0.35-0.38 nm, and the nitrogen doping content is 1-5 at%.
[0025] The present invention provides a method for preparing a nitrogen-doped closed-cell petroleum coke carbon material, comprising the following steps: grinding and crushing the petroleum coke and an alkali activator, and then placing the mixture under inert atmosphere for high-temperature activation pretreatment. The product after high-temperature treatment is pickled with hydrochloric acid to obtain a carbon material with a developed open-pore structure. The product and a coating reagent, dopamine hydrochloride, are added to an alkaline buffer solution, mixed and stirred at room temperature for reaction, and washed until the pH is neutral after the reaction is completed. The above-mentioned coated product is carbonized at high temperature under inert conditions to obtain the nitrogen-doped closed-cell petroleum coke carbon material. Since petroleum coke is a soft carbon precursor, direct carbonization easily forms a highly graphitized microcrystalline carbon material, which exhibits extremely poor sodium storage performance. Therefore, the present invention first activates the petroleum coke, forms a loose and porous structure through alkali activation, greatly improves the specific surface area and disorder of the petroleum coke-based carbon material, and further stirs and mixes the activated product with the doping coating reagent dopamine hydrochloride in an alkaline buffer solution, and the dopamine hydrochloride undergoes in-situ polymerization to form polydopamine, which contains abundant nitrogen elements. At the same time, the polydopamine molecular chain also contains abundant active groups such as catechol and amino groups, which can be tightly attached to the surface of the material through hydrogen bonds, covalent bonds, etc., so polydopamine has excellent viscosity, can adhere to and block the developed pore structure of the activated product and simultaneously realize uniform nitrogen doping in the activated product; in the subsequent high-temperature carbonization treatment, the pore structure of the activated product is further closed, and finally a nitrogen-doped closed-pore petroleum coke carbon material with a suitable closed-pore structure and excellent sodium storage performance is formed. Compared with petroleum coke directly carbonized at high temperature, the electrochemical performance of the nitrogen-doped closed-cell petroleum coke carbon material of the present invention is significantly improved. Experimental results show that when the nitrogen-doped closed-cell petroleum coke carbon material prepared by the preparation method provided by the present invention is used as the negative electrode of a sodium ion battery, the electrochemical performance of the nitrogen-doped closed-cell petroleum coke carbon material is significantly improved at 0.03Ag -1 At a current density of 1.34 W, its specific capacity can reach 352.8 mAh g -1 , the first coulombic efficiency is 81.3% at 0.06Ag -1 At a current density of , the capacity retention rate is 98.5% after 100 cycles.
[0026] The method of the present invention has a simple preparation process, realizes the high-value-added development and utilization of low-value petroleum coke, and has good application development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope (SEM) image of the nitrogen-doped closed-cell petroleum coke material described in Example 1;
[0028] Figure 2 This is a high-resolution transmission electron microscopy scanning test (HRTEM) image of the nitrogen-doped closed-cell petroleum coke carbon material described in Example 1;
[0029] Figure 3 Isothermal adsorption curves of the two materials described in Example 1 and Comparative Example 2;
[0030] Figure 4 X-ray photoelectron spectra of the two materials described in Example 1 and Comparative Example 2;
[0031] Figure 5 The X-ray diffraction spectrum (XRD) of the nitrogen-doped closed-cell petroleum coke material described in Example 1;
[0032] Figure 6 This is a scanning electron microscope (SEM) image of the material of Comparative Application Example 1 described in Comparative Example 1;
[0033] Figure 7 This is a high-resolution transmission electron microscopy scanning test (HRTEM) image of the material of comparative application example 1 described in comparative example 1;
[0034] Figure 8 This is a scanning electron microscope (SEM) image of the material of Comparative Application Example 2 described in Comparative Example 2;
[0035] Fig. 9 A high-resolution transmission electron microscopy scanning test (HRTEM) image of the material of comparative application example 2 described in comparative example 2;
[0036] Fig.10 The charge-discharge curves of the 1st, 2nd and 3rd cycles of the material of Comparative Application Example 1 described in Comparative Example 1 are shown;
[0037] Fig.11 The charge and discharge curves of the material of comparative application example 2 described in comparative example 2 at the 1st, 2nd and 3rd cycles;
[0038] Fig.12 This is a charge and discharge curve diagram of the nitrogen-doped closed-cell petroleum coke material described in Example 1 at the 1st, 2nd and 3rd cycles.
[0039] Fig.13 This is a charge and discharge curve diagram of the nitrogen-doped closed-cell petroleum coke material described in Example 2 at the 1st, 2nd and 3rd cycles.
[0040] Fig.14 This is a charge and discharge curve diagram of the nitrogen-doped closed-cell petroleum coke material described in Example 3 at the 1st, 2nd and 3rd cycles. DETAILED DESCRIPTION
[0041] The technical solution provided by the present invention is further clearly and completely explained below by way of specific embodiments.
[0042] The present invention provides a method for preparing a nitrogen-doped closed-cell petroleum coke material, comprising the following steps:
[0043] Activation step: grind and mix the petroleum coke and the alkali activator and place them under inert atmosphere for high temperature activation pretreatment. The product after high temperature treatment is pickled with hydrochloric acid to obtain a carbon material with a developed open pore structure.
[0044] Doping and coating step: Add the prepared carbon material with developed open-pore structure and coating agent dopamine hydrochloride into an alkaline buffer solution, mix and stir to react at room temperature, and wash until the pH is neutral after the reaction is completed. Carbonize the above-mentioned coated product at high temperature under inert conditions to obtain a nitrogen-doped closed-pore petroleum coke carbon material.
[0045] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0046] In the present invention, the petroleum coke is spherical calcined coke, and any one of high-sulfur coke, medium-sulfur coke and low-sulfur coke can be selected.
[0047] The activator can be sodium hydroxide or potassium hydroxide, and the mass ratio of petroleum coke to the alkaline activating agent is 1:0.5-1:4; the coating agent is dopamine hydrochloride; and the alkaline solution is Tris-HCl buffer.
[0048] In the present invention, the activator and petroleum coke only need to be simply ground and mixed. The activator melts and etches the petroleum coke during the high-temperature activation process to form a rich pore structure, thereby increasing the specific surface area and disorder of the petroleum coke. The temperature of the high-temperature activation pretreatment is preferably 400-900°C, more preferably 600-800°C. The heating rate to the high-temperature activation treatment is preferably 2-10°C / min. The high-temperature activation pretreatment is carried out under an inert atmosphere, and the inert atmosphere is preferably nitrogen, helium or argon. After the high-temperature activation treatment, the activated product should be acid-washed, then washed to neutrality and then dried. The doping coating reagent is dopamine hydrochloride, and the quality of the activated product is related to the The mass ratio of the doping and coating reagents is preferably 1:1-1:6, more preferably 1:1-1:3; the activated product and the doping and coating reagent are mixed and stirred in an alkaline buffer solution at room temperature for 10-40 hours, and the stirring speed is 200-800r / min; the alkaline solution is Tris-HCl buffer; the carbonization temperature of the doping and coating product is preferably 800-1600°C, more preferably 1200-1400°C, and the insulation time is 1-3h; the heating rate to the high-temperature carbonization treatment temperature is 2-10°C / min; the atmosphere of the high-temperature carbonization treatment is an inert atmosphere; the gas of the inert atmosphere is preferably nitrogen, helium or argon.
[0049] The cooling, pickling, washing, filtration and drying steps involved in the present invention are not particularly limited, and the processes well known to those skilled in the art can be used. In the present invention, the temperature of high-temperature activation pretreatment is preferably 400-900°C, more preferably 600-800°C, the temperature of high-temperature carbonization is preferably 800-1600°C, more preferably 1200-1400°C, and the insulation time is 1-3h. In the present invention, when the rotation speed and time of the mixing and stirring, and the temperature and time of carbonization are within the above range, the pore structure of the activated product can be fully closed, and the nitrogen element can be fully and evenly doped to obtain the nitrogen-doped closed-cell petroleum coke material.
[0050] The present invention has no special limitation on the application method of the nitrogen-doped closed-cell petroleum coke carbon material, and the application method of the carbon material in the negative electrode material of a sodium ion battery well known to those skilled in the art can be adopted.
[0051] The following is a detailed description of a method for preparing a nitrogen-doped closed-cell petroleum coke material provided by the present invention in conjunction with an embodiment. The described embodiments are only some embodiments of the present invention and do not include all embodiments of the present invention. Based on some embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] (1) 1.00 g of ground low-sulfur coke powder was mixed with 2.00 g of sodium hydroxide reagent and ground evenly. Under argon atmosphere, the temperature was raised to 650° C. at a heating rate of 5° C. / min, and the mixture was kept warm for 2 h. After cooling, a mixture (2.81 g) was obtained.
[0054] (2) The mixed product in (1) was mixed with 90 ml of hydrochloric acid (1 mol / L) and allowed to stand for 10 h. The mixed solution was then vacuum filtered and washed with deionized water until the solution was neutral. The product was dried in a conventional oven at 120° C. for 10 h to obtain an activated product (0.60 g);
[0055] (3) Take 0.50 g of the activated product obtained in (2) and 1.00 g of dopamine hydrochloride, add them to 40 ml of Tris-HCl alkaline buffer solution, mix and stir at room temperature for 20 h, and the stirring speed is 500 r / min; after mixing and stirring, filter and wash the mixture until it is neutral, and dry it in an ordinary oven at 120°C for 10 h to obtain a doped coated product (0.63 g).
[0056] (4) The coated product obtained in (3) was ground and pulverized, and heated to 1300° C. at a heating rate of 5° C. / min under argon atmosphere, and kept at this temperature for 2 h. After cooling, the nitrogen-doped closed-cell petroleum coke material (0.55 g) of Example 1 was obtained;
[0057] The nitrogen-doped closed-cell petroleum coke material of Example 1 was subjected to an electron microscope scanning test. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the microstructure of the nitrogen-doped closed-cell petroleum coke material of Example 1 is composed of irregular block particles with a particle size of 2 to 30 μm, and there is no pore structure on the surface of the block particles.
[0058] The material of Example 1 was subjected to high-resolution transmission electron microscopy scanning test. The test results are as follows: Figure 2 As shown by Figure 2 It can be seen that the graphite lattice stripes of the nitrogen-doped closed-cell petroleum coke carbon material in Example 1 are disordered, and a large number of micropores are distributed in the material, and most of the micropores are closed-cell structures with a high degree of disorder.
[0059] The two materials of Example 1 and Comparative Example 2 were subjected to nitrogen adsorption / desorption tests. The test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the pore volume of the nitrogen-doped closed-cell petroleum coke carbon material in Example 1 is 0.026 cm 3 g -1 , the specific surface area is only 23m 2 g -1 , while the pore volume of the material in Comparative Example 2 is 0.680 cm 3 g -1 , with a specific surface area of 1422m 2 g -1 .
[0060] The two materials prepared in Example 1 and Comparative Example 2 were tested using an X-ray photoelectron spectrometer, and the XPS graphs were as follows: Figure 4 As shown. Figure 4 From the XPS graph, it can be seen that the two materials prepared in Example 1 and Comparative Example 2 have two obvious peaks at ~285 and ~533 eV, corresponding to the C element and the O element, while at ~401 eV only the material of Example 1 has a more obvious peak, corresponding to the N element, and the N element content accounts for 2.60%.
[0061] The nitrogen-doped closed-cell petroleum coke material prepared in Example 1 was tested using an X-ray diffractometer, and the XRD pattern was as follows: Figure 5 As shown. Figure 5 The XRD spectrum of the obtained results showed that the interlayer spacing of the (002) crystal plane of the nitrogen-doped closed-cell petroleum coke carbon material prepared in Example 1 was relatively small, which was 0.36 nm.
[0062] Example 2
[0063] The other conditions are the same as those in Example 1, except that the activated product and dopamine hydrochloride are mixed and stirred in Tris-HCl buffer for 10 hours. After a series of treatments, the nitrogen-doped closed-cell petroleum coke material of Example 2 is obtained.
[0064] Example 3
[0065] (1) 1.00 g of the ground medium sulfur coke powder was mixed with 2.00 g of potassium hydroxide reagent and ground evenly. The mixture was heated to 750° C. at a heating rate of 5° C. / min under the protection of a helium atmosphere, kept at this temperature for 2 h, and cooled to obtain a mixture (2.57 g);
[0066] (2) The mixed product in (1) was mixed with 90 ml of hydrochloric acid (1 mol / L) and allowed to stand for 10 h. The mixed solution was then vacuum filtered and washed with deionized water until the solution was neutral. The product was dried in a conventional oven at 120° C. for 30 h to obtain a doped activated product (0.50 g);
[0067] (3) Take 0.50 g of the activated product obtained in (2) and 1.50 g of dopamine hydrochloride, add them to 40 ml of Tris-HCl alkaline buffer solution, mix and stir at room temperature for 30 hours, and the stirring speed is 500 r / min; after mixing and stirring, the mixture is filtered and washed until neutral, and dried in an ordinary oven at 120°C for 10 hours to obtain a coated product (0.69 g).
[0068] (4) The coated product obtained in (3) was ground and pulverized, and heated to 1300° C. at a heating rate of 5° C. / min under helium atmosphere, and kept at this temperature for 2 h. After cooling, the nitrogen-doped closed-cell petroleum coke material (0.60 g) of Example 2 was obtained;
[0069] Comparative Example 1
[0070] Take 1 g of low-sulfur coke, grind it into powder, and under the protection of argon atmosphere, heat it to 1300°C at a heating rate of 5°C / min, and carbonize it at a constant temperature for 2 hours to obtain the material of comparative application example 1 (0.88 g).
[0071] The material of comparative application example 1 was subjected to electron microscope scanning test, and the test results are as follows Figure 6 As shown by Figure 6 It can be seen that the microscopic morphology of the material of Comparative Application Example 1 is composed of irregular block particles with a particle size of 2 to 10 μm and fine particles <1 μm, which vary in size.
[0072] The material of comparative application example 1 was subjected to high-resolution transmission electron microscope scanning test. The test results are as follows: Figure 7 As shown by Figure 7 It can be seen that the material of comparative application example 1 exhibits relatively ordered graphite lattice stripes.
[0073] Comparative Example 2
[0074] (1) 1.00 g of ground low-sulfur coke powder was mixed with 2.00 g of sodium hydroxide reagent and ground evenly. Under argon atmosphere, the temperature was raised to 650° C. at a heating rate of 5° C. / min, and the mixture was kept warm for 2 h. After cooling, a mixture (2.81 g) was obtained.
[0075] (2) The mixed product in (1) was mixed with 90 ml of hydrochloric acid (1 mol / L) and allowed to stand for 10 h. The mixed solution was then vacuum filtered and washed with deionized water until the solution was neutral. The product was dried in a conventional oven at 120° C. for 10 h to obtain an activated product (0.60 g);
[0076] (3) The activated product obtained in (2) was ground and pulverized, and the temperature was raised to 1300° C. at a heating rate of 5° C. / min under argon atmosphere, and carbonized at a constant temperature for 2 h to obtain the material of comparative application example 2 (0.56 g);
[0077] The material of comparative application example 2 was subjected to electron microscope scanning test, and the test results are as follows: Figure 8 As shown. Figure 8 It can be seen that the microscopic morphology of the material of comparative application example 2 is composed of irregular block particles with a particle size of 2 to 10 μm, and a uniform and rich pore structure of <5 μm is distributed on the surface of the block particles.
[0078] The material of comparative application example 2 was subjected to high-resolution transmission electron microscope scanning test. The test results are as follows: Fig. 9 As shown by Fig. 9 It can be seen that the graphite lattice stripes of the material in comparative application example 2 are disordered, and it can be seen that the material is rich in micropores, and most of the micropores are open-pore structures with a high degree of disorder.
[0079] Test Case
[0080] The nitrogen-doped closed-cell petroleum coke material prepared in Comparative Example 1-2 and Example 1-3 was mixed with sodium carboxymethyl cellulose in a mass ratio of 95:5, and water was used as a dispersant. The mixture was uniformly mixed in a homogenizer to form a slurry. The slurry was uniformly scraped onto the current collector copper foil, and after drying in an oven, it was cut into (10×10) mm 2 The electrode was placed in a vacuum oven and vacuum dried at 120°C for 10 hours. The mass was weighed and transferred to a glove box. In an argon atmosphere, sodium metal was used as the counter electrode, and 1M NaClO4 was dissolved in 1L of ethylene carbonate and diethyl carbonate solution with a volume ratio of 1:1 as the electrolyte. A CR2025 button cell was assembled in an argon atmosphere.
[0081] The assembled CR2025 button cell was subjected to charge and discharge performance tests under the following test conditions: the current density was set to 0.1C (1C = 300 mA g -1 );Discharge cut-off voltage is 0.001V, and charge cut-off voltage is 2.5V.
[0082] Fig.10 The charge-discharge curves of the material prepared in Comparative Example 1 at the 1st, 2nd and 3rd cycles; Fig.10 It can be seen that the reversible specific capacity of the material described in Comparative Example 1 is 155.7 mAh g -1 , the first coulombic efficiency is 72.5%;
[0083] Fig.11 The charge-discharge curves of the material prepared in Comparative Example 2 at the 1st, 2nd and 3rd cycles; Fig.11 It can be seen that the reversible specific capacity of the material described in Comparative Example 2 is 163.2 mAh g -1 , the first coulombic efficiency is 28.3%;
[0084] Fig.12 The charge-discharge curves of the nitrogen-doped closed-cell petroleum coke material prepared in Example 1 at the 1st, 2nd and 3rd cycles; Fig.12 It can be seen that the reversible specific capacity of the nitrogen-doped closed-cell petroleum coke carbon material described in Example 1 is 352.8 mAh g -1 , the first coulombic efficiency is 81.3%;
[0085] Fig.13 The charge-discharge curves of the nitrogen-doped closed-cell petroleum coke material prepared in Example 2 at the 1st, 2nd and 3rd cycles; Fig.13 It can be seen that the reversible specific capacity of the nitrogen-doped closed-cell petroleum coke carbon material described in Example 2 is 275.4 mAh g -1 , the first coulombic efficiency is 70.7%;
[0086] Fig.14 The charge-discharge curves of the nitrogen-doped closed-cell petroleum coke material prepared in Example 3 at the 1st, 2nd and 3rd cycles; Fig.14 It can be seen that the reversible specific capacity of the nitrogen-doped closed-cell petroleum coke carbon material described in Example 3 is 331.0 mAh g -1 , the first coulombic efficiency is 82.5%;
[0087] The electrochemical test performances of the petroleum coke-based carbon materials of Comparative Examples 1-2 and Examples 1-3 are summarized in Table 1 below.
[0088] Table 1 Electrochemical test performance of petroleum coke-based carbon materials of Examples 1-3 and Comparative Examples 1-2
[0089]
[0090] It can be seen from the above experimental test results that the nitrogen-doped closed-cell petroleum coke material prepared by the present invention has excellent sodium storage capacity and coulombic efficiency.
Claims
1. A method for preparing a nitrogen-doped closed-cell petroleum coke negative electrode material, characterized in that: The following steps are involved: (1) Activation step: The petroleum coke and the alkaline activator are ground and mixed and then placed under inert atmosphere for high temperature activation pretreatment. The product after high temperature treatment is pickled with hydrochloric acid to obtain a carbon material with a developed open pore structure. (2) Doping and coating step: Add the prepared carbon material with developed open-pore structure and the coating agent dopamine hydrochloride into an alkaline buffer solution, mix and stir to react at room temperature, and wash until the pH is neutral after the reaction is completed. Carbonize the above-mentioned coated product at high temperature under inert conditions to obtain a nitrogen-doped closed-pore structure carbon material.
2. The method according to claim 1, characterized in that The petroleum coke is spherical calcined coke, and any one of high-sulfur coke, medium-sulfur coke and low-sulfur coke can be selected.
3. The method according to claim 1, characterized in that The activator can be sodium hydroxide or potassium hydroxide, and the mass ratio of petroleum coke to the alkali activating agent is 1:0.5-1:4; Preferably, the mass ratio of the petroleum coke to the activation reagent is 1:1-1:
3.
4. The method according to claim 1, characterized in that The temperature of the high temperature activation pretreatment is 400-900°C and the time is 1-3h; Preferably, the high-temperature activation pretreatment is carried out in an inert atmosphere, and the gas of the inert atmosphere is nitrogen, helium or argon; Preferably, the heating rate to the high temperature activation pretreatment temperature is 2-10° C. / min.
5. The method according to claim 1, characterized in that The coating reagent is dopamine hydrochloride; The mass ratio of the activated product to the coating reagent is 1:1-1:
6.
6. The method according to claim 5, characterized in that The activated product and the coating reagent are mixed and stirred in an alkaline buffer solution Tris-HCl at room temperature for 10-40 hours, and the rotation speed of the stirring process is 200-800 r / min.
7. The method according to claim 1, characterized in that The carbonization temperature of the coated product is 800-1600° C., preferably 1200-1400° C., and the insulation time is 1-3 hours.
8. The nitrogen-doped closed-cell petroleum coke material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The pore volume of the nitrogen-doped closed-cell petroleum coke carbon material is 0.01-0.03 cm 3 g -1 , with a specific surface area of 1-25m 2 g -1 The (002) crystal plane interlayer spacing of the nitrogen-doped closed-cell petroleum coke carbon material is 0.35-0.38 nm, and the nitrogen doping content is 1-5 at%.
9. An application of a sodium ion battery, characterized in that: The nitrogen-doped closed-pore petroleum coke material according to claim 1 is used as the negative electrode material of the sodium ion battery.
Citation Information
Patent Citations
A low-temperature petroleum coke anode material with nitrogen-containing polymer pyrolytic carbon coated on its surface and its preparation method
CN106684367B
High-sulfur petroleum coke derived porous carbon, preparation method thereof, electrode material and sodium ion battery
CN117923459A